2022
DOI: 10.1021/acssuschemeng.1c07261
|View full text |Cite
|
Sign up to set email alerts
|

Liberation and Separation of Ultrafine Tungsten Carbide Particles from an Activated Carbon Substrate

Abstract: Production of fine-grained tungsten carbide is expensive due to the energy-intensive techniques employed in traditional commercial operations. Recent research has shown that ultrafine (<2 μm) tungsten carbide particles can be produced by the adsorption of tungstate oxyanions on an activated carbon substrate followed by reduction and carburization at elevated temperature under a controlled furnace atmosphere. The thermal processing step is effective at temperatures substantially lower than those used in commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…In electrophysiological systems, noise is characterized as any disturbance that hinders the accurate measurement of the signal, causing it to deviate from its true measured value. 7 Within these systems, signal disruptions may arise from various sources, including acoustic and electromagnetic interference present in the laboratory environment where experiments are con-ducted�classified as external sources. Additionally, the amplifier itself can introduce disturbances in the form of electromagnetic waves, which constitute internal noise.…”
Section: Noise Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…In electrophysiological systems, noise is characterized as any disturbance that hinders the accurate measurement of the signal, causing it to deviate from its true measured value. 7 Within these systems, signal disruptions may arise from various sources, including acoustic and electromagnetic interference present in the laboratory environment where experiments are con-ducted�classified as external sources. Additionally, the amplifier itself can introduce disturbances in the form of electromagnetic waves, which constitute internal noise.…”
Section: Noise Measurementmentioning
confidence: 99%
“…However, in contrast to biological nanopores, solid-state nanopores offer the advantage of facilitating the fabrication of robust nanopores . Previous research has demonstrated the considerable challenge in separating and characterizing inorganic particles <2 μm, primarily due to limitations posed by particle density and centrifugation methods . It is noteworthy that, for instance, the centrifugation process can lead to the breakage and fragmentation of delicate DNA polymer molecules .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation